Orbital facilitated charge transfer originated phonon mode in Cr‐substituted PrFeO3: A brief Raman study. (27th April 2020) - Kumar, Anil; Umrao, Sima; Sagdeo, Pankaj R.
Abstract: We report the possible origin of orbital facilitated new Raman mode in orthorhombic perovskite PrFe1‐x Crx O3 . For this purpose, resonance and power‐dependent Raman spectroscopy measurements have been carried out to understand the origin of local oxygen breathing mode in the mixed Fe–Cr orthorhombic perovskites through the orbital mediated charge transfer mechanism. It has been observed that multi‐phonon scattering is highly sensitive to the presence of mixed Fe–Cr ions and is absent in pure iso‐structural vacuum annealed PrFeO3 . The Raman spectroscopy results infer a scaling in the intensity of octahedral breathing Raman mode around 660 cm −1, which is attributed to the lattice rearrangement due to the transfer of an electron from Cr 3+ ( d 3 ) to Fe 3+ ( d 5 ) and results to d 2 –d 6 (Cr 4+ –O −2 –Fe 2+ ) configuration. The interactions of d 2 –d 6 configuration are different from d 3 –d 5 configuration, which leads to the octahedral lattice rearrangement and activates the new Raman mode. The charge transfer phenomenon is supported through first‐principle calculations and valence band spectroscopy. Abstract : Orbital mediated Franck–Condon mechanism for mixed Fe–Cr system, Vg0, Vg1, Vg2, … Vgn and Ve0, Ve1, Ve2, … Ven, represents the vibrational states of Cr 3+ and Fe +3, respectively. For Franck–Condon scattering to happen, the vibrational ground state must coincide with any virtual vibrational state of electronically excited state. The lattice distortion arises due to orbital mediated charge transfer from Cr 3+ to Fe 3+ is shown by δ.